Soluble proteins of chemical communication: an overview across arthropods - Pelosi, Paolo; Iovinella, Immacolata; Felicioli, Antonio; Dani, Francesca R. (Frontiers in Physiology, 2014)
Detection of chemical signals both in insects and in vertebrates is mediated by soluble proteins, highly concentrated in olfactory organs, which bind semiochemicals and activate, with still largely unknown mechanisms, specific chemoreceptors. The same proteins are often found in structures where pheromones are synthesised and released, where they likely perform a second role in solubilising and delivering chemical messengers in the environment. A single class of soluble polypeptides, called Odorant-Binding Proteins (OBPs) is known in vertebrates, while two have been identified in insects, OBPs and CSPs (Chemosensory Proteins). Despite their common name, OBPs of vertebrates bear no structural similarity with those of insects. We observed that in arthropods OBPs are strictly limited to insects, while a few members of the CSP family have been found in crustacean and other arthropods, where however, based on their very limited numbers, a function in chemical communication seems unlikely. The question we address in this review is whether another class of soluble proteins may have been adopted by other arthropods to perform the role of OBPs and CSPs in insects. We propose that lipid-transporter proteins of the Niemann-Pick type C2 family could represent likely candidates and report the results of an analysis of their sequences in representative species of different arthropods.